The Last Castaways - Horse H. Harry (London, Puffin Books, 2003)
Grandfather is off on an expedition to the North Pole to find the Last Polar Bears and with him goes Roo - a dog of character and strong views. The intrepid explorers set sail on the good ship Unsinkable and embark on the adventure of a lifetime. Eccentric, moving and very funny, their story is told through a series of extraordinary letters.